2018
DOI: 10.22146/jpsi.25011
|View full text |Cite
|
Sign up to set email alerts
|

Peran Dukungan Sosial Keluarga, Atasan, dan Rekan Kerja terhadap Resilient Self-Efficacy Guru Sekolah Luar Biasa

Abstract: This study aimed to investigate the influence of social support from family, supervisor, and co-workers toward the resilient self-efficacy of SEN teachers in Surabaya. This study involved 94 SEN teachers from Special Educational Needs school in Surabaya. The study used social support measures and resilient self-efficacy scale. Multiple regression analysis showed that social support from family, supervisor, and co-workers significantly influenced SEN teachers' resilient self-efficacy (F = 28,052; p<0,05). These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
3
1
7
Order By: Relevance
“…Based on the explanation above, it can be concluded that co-worker social support has significant role towards resilient self-efficacy of psychiatric hospital nurses compared to supervisor social support. The conclusion of this study is different with Santoso and Setiawan (2018) findings which showed that supervisors played significant role towards resilient self-efficacy of special needs teachers. Supervisors had a role in providing informational and emotional supports which formed closeness between supervisors and special need teachers.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Based on the explanation above, it can be concluded that co-worker social support has significant role towards resilient self-efficacy of psychiatric hospital nurses compared to supervisor social support. The conclusion of this study is different with Santoso and Setiawan (2018) findings which showed that supervisors played significant role towards resilient self-efficacy of special needs teachers. Supervisors had a role in providing informational and emotional supports which formed closeness between supervisors and special need teachers.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, if social co-worker social support was provided separately, there was significant influence towards resilient self-efficacy of psychiatric hospital nurses. Different form of relationship between nurse and sources of support will have different effects (Santoso & Setiawan, 2018). It can be concluded that co-workers become valuable people for nurses when experiencing problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kehidupan manusia sebagai makhluk sosial, tidak jauh dari apa yang disebut dengan proses interaksi sosial. Dalam lingkungan sosial proses ini terjadi antara satu orang dengan yang lain atau orang dengan kelompok, kelompok dengan kelompok yang lain atau dapat disimpulkan bahwa ketika manusia dan kelompok sosial ada, maka terdapat hubungan timbal balik dan proses interaksi sosial ada seperti berbicara melalui bahasa atau tindakan fisik lainnya (Santoso, 2014).…”
Section: Pendahuluanunclassified
“…Dari berbagai faktor yang menyebabkan tingkat resiliensi berbeda pada individu, faktor eksternal yaitu dukungan sosial dianggap menjadi salah satu faktor penting dalam membangun resiliensi terutama bagi tenaga kesehatan, karena dianggap mampu melindungi dari stres dan cemas Zimet, dan Farley (1988) penerimaan dukungan sosial didefinisikan sebagai persepsi individu tentang bagaimana sumber daya dapat bertindak sebagai penahan antara peristiwa dan gejala stres, yang bersumber dari (1) keluarga meliputi orang tua, pasangan, mertua, saudara (Astuti, Santosa, & Utami, 2000;Fatima, Sharif, & Zimet, 2018); (2) teman, meliputi orang terdekat dengan usia yang tidak jauh berbeda, memiliki hubungan erat, misal teman sekolah, tetangga dan (3) significant others adalah dukungan yang bersumber dari seseorang yang dianggap penting tergantung pada jaringan sosial yang ada, sebagai contoh meliputi rekan kerja, atasan (Santoso & Setiawan, 2018). Beberapa penelitian terdahulu menyatakan bahwa tenaga kesehatan yang menerima dukunga sosial cenderung memiliki resiliensi yang tinggi, yang juga meningkatkan control terhadap perasaan negatif terhadap kondisi penuh tekanan (Kılınç & Çelik, 2020).…”
Section: Pendahuluanunclassified